Public participation in health systems in Zimbabwe - Loewenson, Rene (2000)
Outlines some of the challenges faced in moving away from a health system largely planned and governed by technical personnel to one that involves wider public participation and accountability in planning, implementing and monitoring health services. Considers factors that contribute to motivation for changes in approach and towards a greater degree of community participation in mechanisms for and the governance of health service delivery.